A comparison of periodization models during nine weeks with equated volume and intensity for strength - Buford, T. W.; Rossi, S. J.; Smith, D. B.; Warren, A. J. (The Journal of Strength and Conditioning Research, 2007)
The purpose of the present investigation was to determine if significant differences exist among 3 different periodization programs in eliciting changes in strength. Twenty-eight recreationally trained college-aged volunteers (mean = SD; 22.29 = 3.98) of both genders were tested for bench press, leg press, body fat percentage, chest circumference, and thigh circumference during initial testing. After initial testing, subjects were randomly assigned to 1 of 3 training groups: (a) linear periodization (n = 9), (b) daily undulating periodization (n = 10), or (c) weekly undulating periodization (n = 9). The training regimen for each group consisted of a 9-week, 3-day-per-week program. Training loads were assigned as heavy (90%, 4 repetition maximum [4RM]), medium (85%, 6RM), or light (80%, 8RM) for bench press and leg press exercises. Subjects were familiarized with the CR-10 rated perceived exertion scale and instructed to achieve an 8 or 9 on the final repetition of each set for all other exercises. Subjects were then retested after 4 weeks of training. Training loads were then adjusted according to the new 1RM. Subjects were then retested after 5 more weeks of exercise. For all subjects, significant (p < 0.05) increases in bench press and leg press strength were demonstrated at all time points (T1-T3). No significant differences (p > 0.05) were observed between groups for bench press, leg press, body fat percentage, chest circumference, or thigh circumference at all time points. These results indicate that no separation based on periodization model is seen in early-phase training.